2019
DOI: 10.1111/wrr.12762
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between vitamin D and diabetic foot disease? A meta‐analysis

Abstract: It has been demonstrated that Vitamin D (25(OH)D) deficiency is associated with diabetes and with diabetic neuropathy. Some reports stated that vitamin D deficiency is also associated with diabetic foot ulcer and/or infection. Knowing the beneficial effect of vitamin D on wound healing, a quantitative evidence synthesis is needed to look for such association. Medline, Embase, Scopus, CINAHL, Cochrane Library, and Google Scholar were searched for from inception. The outcomes were set to be either the serum 25(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU (17,20,45,54,55). We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU (17,20,45,54,55). We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 59%
“…DR and DKD are common microvascular complications of diabetes ( 7 ). Many clinical studies have recognized VDD as the risk factor for DR ( 16 , 25 , 41 ) and DKD ( 17 , 42 ), whereas other epidemiological researches showed opposite results ( 21 , 22 , 43 ). In this study, we revealed that the correlation between VDD status and the prevalence of DR or DKD was not statistically significant after adjusting laboratory measurements, diabetic complications, related comorbidities, and medications besides the adjustment for demographics and physical measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies have revealed that patients with DFU had higher prevalence of VDD and lower vitamin D levels in comparison to diabetic patients without DFU [17,22,70,[80][81][82]. We reported that the prevalence of VDD in participants with DFU was about 80%.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to mediating bone metabolism by regulating calcium and phosphorus homeostasis, vitamin D also modulates cell proliferation, differentiation, apoptosis, immune function, inflammation response, as well as vascular and metabolic properties (e.g., insulin secretion and insulin sensitivity) [12][13][14]. In the past few years, the association between vitamin D deficiency (VDD) and other nonclassical outcomes besides skeletal disorders has drawn increasing attention, especially diabetes and diabetes-related complications [14][15][16][17]. Although the inverse association between vitamin D levels and risk of T2DM [18,19], DR [20], DKD [21], or DFU [22] among diverse populations has been reported, uncertainties still exist due to the discordant results [23,24].…”
Section: Introductionmentioning
confidence: 99%